Calculated Blood Loss and Transfusion Requirements in Primary Open Repair of Craniosynostosis. Issue 2 (February 2019) - Lopez, Marcos M.; Lee, James; Morrison, Kerry; Hoffman, Caitlin; Souweidane, Mark; Ascherman, Jeffrey A.
Abstract : Background: Open surgical correction is effective in the treatment of craniosynostosis but may result in significant blood loss and transfusions. This study seeks to compare surgeon estimated blood loss with calculated blood loss and provide contemporary data that objectively quantify blood loss and transfusion rate associated with open repair of craniosynostosis. Methods: A retrospective review of patients undergoing primary open repair of craniosynostosis between May 2011 and November 2016 was performed. The medical records of 43 patients were reviewed to obtain the operative age, weight, affected suture, pre- and postoperative hematocrit, blood transfusion volume, estimated blood loss, and syndromic status. Estimated blood volume (EBV) and red cell mass were calculated for analysis. Results: The median age and weight at the time of surgery were 9 months and 8.6 kg, respectively. Mean surgeon estimated blood loss was 207.4 mL (28.1% of EBV). Mean calculated blood loss was 318 mL (44.3% of EBV). The mean transfusion volume was 188 mL (26.5% of EBV). The mean transfusion as a percent of estimated red cell mass was 59.1%. Fourteen percent of patients did not require any transfusion. Conclusions: We report intraoperative blood losses and transfusion requirements that are lower than those of many previous studies of open repair of craniosynostosis. Additionally, we found that calculated blood loss estimates may be more reliable than surgeon-derived estimated blood loss. We hope that these updated, objective data will be useful in comparisons of open repair to minimally invasive surgery or to new blood loss reducing procedures.